Proses Re-Desain dan Perbaikan Furnace Dengan Daya 5000 W: Re-Design and Repair Process of 5000 W Furnace - I Wayan Sugita; Ferry Budhi Susetyo; Hanapi; Moh Sahal Rifai (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2022)
Re-design and repair of the furnace with a power consumption of 5000Watt was carried out to repair and add parts of the existing furnace. This is done so that the old furnace can be refined in its usefulness. In the re-design process, there are several stages, starting with the stage of making a sketch of the drawing, the size of the frame, the combustion chamber, and continuing at the stage of making working drawings. Next is the analysis of the calculation of the amount of heat released and the electricity consumption used. Based on the results of the furnace testing process, it can be concluded that the re-designed and repaired furnace is able to work optimally. The temperature produced by the furnace reaches 833°C within 26 minutes 34 second.